2016
DOI: 10.1007/s00381-016-3107-1
|View full text |Cite
|
Sign up to set email alerts
|

Glial heterotopia of the orbit: a rare cause of proptosis

Abstract: We report a case of a 4-month-old girl presenting congenital proptosis with progressive increase. CT scan revealed an intraorbital mass without bony defect. The patient was operated, and resection was subtotal. Histologically, the tumor was composed of glial tissue with plexus choroid and pathologist concluded glial heterotopia. The child is under constant medical supervision because recurrences can be observed after incomplete resection; she had no new clinical signs at 18 months follow-up.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…The presence of CSF suggests either endogenous production by choroidal plexuses within the mass or exogenous production that reaches the mass through intracranial extension or a leak [3]. Recently, Bakhti et al reported the case of a 4-month-old girl with progressive proptosis since birth [10]. Histopathological analysis of the excised mass revealed the presence of choroid plexus cells within GH.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The presence of CSF suggests either endogenous production by choroidal plexuses within the mass or exogenous production that reaches the mass through intracranial extension or a leak [3]. Recently, Bakhti et al reported the case of a 4-month-old girl with progressive proptosis since birth [10]. Histopathological analysis of the excised mass revealed the presence of choroid plexus cells within GH.…”
Section: Discussionmentioning
confidence: 99%
“…Histopathological analysis of the excised mass revealed the presence of choroid plexus cells within GH. The authors suggested that the progressive proptosis was due to continuous production of CSF within the mass [10]. Call and Baylis reported a case of orbital cerebellar ectopia with CSF leakage from the wound after mass excision.…”
Section: Discussionmentioning
confidence: 99%